Numerical Analysis of Single-Angle Steel Member Under Tension Force with Different End Deformations - Ahmed M. Sayed (Civil Engineering Journal, 2020)
Steel members with a single-angle cross-section are widely used, but some of their behaviours under loads are not considered by design codes, necessitating related research. This study is carried out on fifty steel single-angle members focused on the stress distribution behaviour and the ultimate axial load capacities under different end deformations through 3-dimensional Finite Element (FE) simulations and comparison with previous experimental findings. FE modeling is capable of modeling steel structures with high accuracy. Based on the results, the length of the angle affects neither the shape of the stress distribution nor the ultimate load capacity of the element. The end deformations affect the stress distribution on the member angle cross-section, including the ultimate load capacity. The end deformations which restricted deformations in the two directions perpendicular to the load axis are found to be optimal, with an average increase in load capacity by a factor of 1.96 for an equal angle and 2.21 for an unequal angle compared with the capacities calculated for single angles with deformations allowed in all directions. The appearance of a compression zone on the unconnected angle leg reduces the ultimate load capacity. The current design code (ANSI/AISC-360) can be adopted to calculate the ultimate load in the case of no deformation in the y-axis direction and no deformations in the x- and y-axis directions where the mean ratios of PNum/Pcode are 1.24 and 1.34 respectively. However, the code does not agree with the end deformations of free deformations and no deformation in the x-axis direction for either equal or unequal angles where the mean ratios of PNum/Pcode are 0.64 and 0.79 respectively, which is unsafe.